Oxidative stress as a risk factor for diabetic myopathy in children - O.Ye. Pashkova; N.I. Chudova (Zaslavsky O.Yu., 2021)
Background. The purpose was to determine the pathogenetic role of oxidative stress in the development of diabetic myopathy in children with diabetes mellitus. Materials and methods. The study included 60 children with type 1 diabetes mellitus (DM1), aged 11 to 17 years. Group 1 included 20 patients with a duration of disease less than 1 year. Group 2 consisted of 20 patients with a duration of diabetes from 1 to 5 years. Group 3 was formed of 20 kids with the duration of diabetes over 5 years. The control group consisted of 20 apparently healthy children. All children underwent the skeletal muscle index determination, ultrasound examination of skeletal muscles, and determination of the level of creatine phosphokinase, homocysteine, and nitrotyrosine in the blood serum. Results. According to the conducted ultrasound diagnostics, the DM1 children were found to present a decrease in the mass of skeletal muscles due to a reduced muscle thickness in the dynamics of the disease. It was proved that hyperglycemia in children with DM1 resulted in the significant oxidative stress confirmed by an increase in the blood serum content of homocysteine and nitrotyrosine, and damage to skeletal muscles, which was confirmed by high blood serum levels of creatine phosphokinase, started from 1 year of illness. Significant changes were found in group 3 of children, where high values of homocysteine and nitrotyrosine were determined in comparison with both the control and group 1 of the study (p < 0.05). An inverse correlation was found between the levels of homocysteine, nitrotyrosine, and the skeletal muscle index, respectively (r = -0.39 (p < 0.05); r = -0.35 (p < 0.05)), and the dependence of these indicators on the state of glycemic control. Conclusions. There is a progressively increased activity of creatine phosphokinase from 1 year of DM1, which indicated early damage to the muscle tissue in children with type 1 diabetes mellitus. One of the causes of skeletal muscle damage and the formation of diabetic myopathy in diabetic children is oxidative stress, which increased with poor glycemic control.